Teachers’ and parents’ attitude to relevance of sexuality education of adolescents with mild intellectual disabilities - Povilaitienė, Neringa; Radzevičienė, Liuda (Social Welfare: Interdisciplinary Approach, 2015)
The article deals with teachers’ and parents’ attitudes towards sexuality education of adolescents with mild intellectual disabilities. It is indicated that teachers treat sexuality education as a relevant problem of education of adolescents with mild intellectual disabilities due to pupils and parents’ insufficient knowledge about sexuality education. Informants are particularly concerned about pupils’ active sex life, which often results in early pregnancy, sexually transmitted diseases, etc. Problems are determined by pupils’ emotional and behavioural problems, lack of social skills, and deepened by the negative impact of the family and environment. During the research, the prevalence of different attitudes of participants of the educational process (parents and teachers) towards sexuality education of adolescents with mild intellectual disabilities in social and educational environment was observed. Teachers state that sexuality education is a relevant problem due to pupils’ early sexual interactions, lack of social skills, emotional and behavioural problems and demonstration of destructive sexual behaviour.
Keywords: sexuality education; disability; adolescents with mild intellectual disabilities; social skills